Neurological effects of ketamine: mechanisms, addiction potential, and toxicity profiles with focus on Saudi Arabia - Albanna, Alanoud K.; Alnefaie, Zayed M.; Saleh, Atheer M.; Alsayedeash, Fatimah H.; Almejmaj, Layan S.; Alturki, Afnan I.; Alnwagha, Rawan K.; Deraa, Fay N. Abu; Sabaa, Narjes Al; Obaid, Ahmed A.; Alayidh, Mazen (International Journal Of Community Medicine And Public Health, 2025)
Ketamine’s rapid action and diverse physiological effects have made it an important drug in both anesthesia and mental health treatment. Clinically, it offers unique dissociative anesthetic properties, preserving stable vital signs during sedation and analgesia. Beyond its numbing effect, studies explore its influence on N-methyl-D-aspartate (NMDA) receptors and wider neurochemical systems linked to its antidepressant action, especially for treatment-resistant depression. While beneficial therapeutically, ketamine’s potential for abuse, especially recreationally, is a concern. Brain imaging reveals structural degeneration in brain areas related to memory, emotion, and motor control, due to chronic misuse, resulting in severe neurological changes. Yet, in controlled settings, ketamine displays potential for addiction treatment, as studies reveal decreased cravings and higher abstinence rates, Toxicity is a worry, particularly when ketamine is taken in large quantities or without medical guidance. Potential effects range from hallucinations and heart problems to difficulties with urination and liver damage. Cognitive impairment and psychiatric symptoms are also seen with prolonged use. While generally safe when used as directed, continued research emphasizes the need for strict clinical supervision and further investigation of its long-term consequences.